ANALISIS INTEGRITAS PEMIMPIN DALAM KELOMPOK SEL BAGI PENINGKATAN ROHANI JEMAAT DI GEREJA BETHEL INDONESIA TABGHA TANJUNG PIAYU BATAM. - Johannes Hutabarat (JURNAL IMPARTA, 2023)
Christian leadership should follow the example of Jesus Christ. Small groups are a biblical pattern that occurs in fulfilling God's grand plan for the salvation of humanity, as demonstrated by Jesus with His twelve disciples. True Christian small groups can lead everyone to become disciples of Jesus by carrying out the Great Commission. The integrity of leaders within small groups is believed to bring spiritual growth to the congregation in the local church, leading more people to come and seek God during worship. This research was conducted with the aim of determining the extent of Leader's Integrity, Small Group, and Spiritual Growth in Tabgha Church in Tanjung Piayu, Batam. After collecting all the data from interviews and observations, the researcher proceeded to analyze the data in accordance with the research methodology outlined in the research chapter. The study found a coherence between words and actions; leaders who hold their duties and responsibilities can achieve predetermined goals. Leaders who adhere to the planned course from the beginning, along with all the risks involved, must possess honesty, responsibility, set an example, have the courage to rebuke those who do wrong, but also courageously praise those who do well according to the given direction. Trustworthy leaders are those who can guide, assign tasks in line with the established objectives, stay focused on those objectives, and provide updates on progress made.